Network Pharmacology-Based Validation of the Efficacy of Huiyangjiuji Decoction in the Treatment of Experimental Colitis - Yu, Wei; Cheng, Hongju; Zhu, Baoliang; Yan, Jing (Frontiers in Pharmacology, 2021)
Objective: Ulcerative colitis (UC) is the major type of inflammatory bowel disease (IBD) characterized by an overactive immune response and destruction of the colorectal epithelium with intricate and extrinsic pathological factors. In China, Huiyangjiuji (HYJJ) decoction has been widely administered against inflammation, but the underlying mechanical mechanism are not known. Methods: A murine model of colitis was established by orally feeding 4% dextran sodium sulfate for 5 days. Intestinal organoids (IOs) were treated with TNFα (Tumor necrosis factor-α) as an ex-vivo UC model. A scratch assay combined with a co-culture system that incubated murine epithelial cell line (IEC-6) with macrophages (Mφs) was utilized to assess epithelial recovery under inflammatory conditions. Network pharmacology analysis was performed to elucidate the mechanism of HYJJ decoction. RNA expression profile of human colorectal cancer cells (DLD-1) with JYJJ was examined by RNA-sequencing. Results: In the present study, we confirmed that HYJJ alleviated the progression of DSS-induced colitis, as evidenced by the improved intestinal injury and fecal albumin, as well as feces blood. Network pharmacology analysis identified the active components in HYJJ formula, and KEGG enrichment analysis indicated that HYJJ-target genes were enriched in pathogen-induced infections, cancer-related as well as inflammatory pathways. Consistently, RNA-sequencing demonstrated that HYJJ treated inhibited cytokine-cytokine interaction, IBD as well as TNF signaling pathways, confirming the anti-inflammatory and anti-neoplastic role of HYJJ decoction. In-vitro experimental evidence confirmed the suppression of pro-interleukins by HYJJ, including IL-2, IL-10 and IL-12. Moreover, the contribution of HYJJ to mucosal healing was corroborated by ex-vivo experiments, in which HYJJ rescued TNFα-compromised IOs functions, i.g., elevated mitochondrial stress (MOS) and impaired regeneration capacity. IEC-6 cells co-culture with Mφs from HYJJ-treated UC mice showed an improved migration capacity as compared to those incubated with UC Mφs. Conclusion: We conclude that HYJJ re-establishes homeostasis of the gut epithelium during colitis by suppressing inflammation and orchestrating cytokines interaction.